The Instability of the Administrative structures and its Effect on The Health Policy in Libya 1977-2000 - Mniena, Mr.Abeer Ibrahim (Dirasat in Economics and Business, 2002)
Different studies of public policies showed that these policies are influenced by the degree of the instability of the administrative structures and institutions. Public Policies studies on Libya arrived to the same conclusion where it was observed that the Libyan political system was characterized by the instability of most of its administrative and political structures and institutions with an adverse effect on the economic , social and educational policies of the regime . This study represents another attempt to trace the effect of structural instability on the monitoring and execution of health policies in Libya. during the period 1977-2000. The study shows that this instability had a negative effect on the health policy in Libya. Some indicators were used to test this proposion. These indicators include: financial allocations to health sector and the actual expenditure , human resources in health sector , and the infrastructures of health sector . The study proves that all these aspects of health policy in Libya were influenced adversely by these administrative and political changes.